2019
DOI: 10.2147/cia.s192050
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations between obesity and cognitive impairment in the Chinese elderly: an observational study</p>

Abstract: Purpose The aim of this study was to investigate the relationship between obesity and cognitive impairment in the Chinese elderly. Patients and methods Patients aged 60 years or above were enrolled from the Department of Geriatrics of The First Affiliated Hospital of Chongqing Medical University from March 2013 to May 2017. Mini-Mental State Examination scale was used to assess the cognitive function. Body mass index (BMI) and waist–hip ratio were used to classify obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 24 publications
7
101
2
3
Order By: Relevance
“…We also did not observe a statistically significant association between obesity and cognitive impairment while Hou et al study had reported that overweight was associated with a decreased risk of cognitive impairment in the elderly, while abdominal obesity was associated with an increased risk of cognitive impairment. 34 Xue et al had reported that diabetes conferred a 1.25-to 1.91-fold excess risk for cognitive disorders. Compared with non-diabetes, diabetes was associated with 49% increased risk of MCI (RR=1.49, 95% CI=1.26-1.77).…”
Section: Discussionmentioning
confidence: 99%
“…We also did not observe a statistically significant association between obesity and cognitive impairment while Hou et al study had reported that overweight was associated with a decreased risk of cognitive impairment in the elderly, while abdominal obesity was associated with an increased risk of cognitive impairment. 34 Xue et al had reported that diabetes conferred a 1.25-to 1.91-fold excess risk for cognitive disorders. Compared with non-diabetes, diabetes was associated with 49% increased risk of MCI (RR=1.49, 95% CI=1.26-1.77).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, there are no studies that aimed to identify potential influential factors in the association between multimorbidity and SCC. Several variables such as obesity 19,20 , smoking 21,22 , alcohol use 23,24 , stress and stressful life events 2527 , depression 28,29 , anxiety 13,30 or sleep problems 31,32 are known to be associated with both multimorbidity and cognitive impairment, and might a play major role in this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obesity in the elderly could exert even more negative effects, for example being a threat to cognitive functionality. In a study on 1100 Chinese subjects aged 60 or above, abdominal obesity was associated to a higher risk of cognitive impairment independently of other environmental factors or metabolic conditions [ 22 ].…”
Section: Metabolic Diseases In the Elderlymentioning
confidence: 99%